Correlation of Progesterone Receptor and Ki-67 Immunomarkers with Histopathological grades of Meningioma - Omair, Sidrah (International Journal of Pathology, 2023)
Back ground: Immunohistochemical markers such as PR and proliferative marker index Ki-67 have considerable prognostic and tumor predictive role in ambiguous cases of meningioma.Objective: To assess Immuno-expression of Progesterone Receptor (PR) & Ki-67 in different histopathological grades of meningioma and to see any correlation between both of these Immuno-markers and WHO grades of meningioma.Material and Methods: This Cross-sectional study was carried out in Pakistan Institute of Medical Sciences (PIMS), Islamabad from September 2017 to August 2018. All neurosurgical biopsies with clinical suspicion of meningioma were processed through various steps. Slides were prepared and stained with Haematoxylin & Eosin (H&E). Immuno-staining with PR & Ki-67 was done after numerous successive steps. Grading of meningioma and Immuno-expression of PR & Ki-67 in all slides were assessed. Data was analyzed using SPSS version 21.Results: Total numbers of cases were 70. Female to male ratio was 1.33. Mean age was 44.34 years. Grade I cases were most common (n=55, 78.6%) followed by Grade II cases (n=12, 17.1%). Grade III cases were the least common (n=3, 4.3%). Among PR Immuno-positive cases, 58.3% were females while 41.4% were males. Overall, 68.6% PR positivity was seen (48/70). Highest PR positivity was seen in grade I cases (78.2%) followed by grade II cases (41.7%) Overall mean Ki-67 for all 70 cases was 5.56%. Lowest mean Ki-67 (3.3%) was seen in Grade I cases and it was higher (12.3%) for grade II cases, while the highest mean Ki-67 (19.7%) was seen in grade III cases.Conclusion: A significant inverse correlation was found between PR and Ki-67 immuno-expression with histopathological grades of meningioma.